(untitled) (Annals of Medical Research, 2021)
Aim: In cases with acute ischemia, albumin’s binding capacity for transition metals decreases and the resulting albumin is defined as ischemia modified albumin (IMA). In this study, we aimed to investigate the relationship between IMA and clinical follow-up in patients with acute renal failure (ARF).Material and Methods: Levels of IMA were measured in 51(23 male, 28 female) patients with ARF. Venous blood samples were drawn from patients for biochemical tests and put in plain tubes containing the gel.Results: Mean age of male and female patients was 65.39±15.28 and 70.11±15.25, respectively. The IMA levels in 25.5% of the patients were within the normal range (400 ABSU) in 75.5% of the patients. The survival rates of patients in IMA 400 ABSU group for 12 and 24 months were 66.7% and for 30 and 32 months it was 33.3%; while the survival rates of patients in IMA ≥400 ABSU group for 12 months were 85.8%, for 24 months were 61.3%, and for 30 and 32 months were 30.6%. No significant difference was determined among survival rates of IMA groups (p=0.719).Conclusion: The comparison between the groups having normal or higher IMA values did not show any significant differences in terms of survival. However, in our study the proportion of patients who needed dialysis during treatment were significantly higher in higher IMA group(IMA≥400 ABSU). Therefore, we believe that higher IMA levels may indicate a necessity for dialysis in patients with ARF.Keywords: Acute Renal Failure; Ischemia Modified Albumin; Acute Kidney Injury.